VIRTUAL REALITY SYSTEM - USE CASE SCENARIO FOR POST-TRAUMATIC STRESS DISORDER SYMPTOMS TREATMENT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This scientific paper presents and focuses on analyzing a system based on virtual reality. The system can be used in multiple fields (such as medicine, art, tourism, archeology, etc.). In this article, we present, as a use case scenario, a medical implementation (with remote secure communication) designed to help and used for people who are affected by post-traumatic stress disorder (PTSD).
Keywords: Virtual reality; Post-traumatic stress disorder; Secure communication; Medical software application; Virtual private network (VPN)